Hydrogen-assisted spark discharge generated metal nanoparticles to prevent oxide formation. Issue 3 (4th March 2018) - Hallberg, R. T.; Ludvigsson, L.; Preger, C.; Meuller, B. O.; Dick, K. A.; Messing, M. E.
ABSTRACT: There exists a demand for production of metal nanoparticles for today's emerging nanotechnology. Aerosol-generated metal nanoparticles can oxidize during particle formation due to impurities in the carrier gas. One method to produce unoxidized metal nanoparticles is to first generate metal oxides and then reduce them during sintering. Here, we propose to instead prevent oxidation by introducing the reducing agent already at particle formation. We show that by mixing 5% hydrogen into the nitrogen carrier gas, we can generate single crystalline metal nanoparticles by spark discharge from gold, cobalt, bismuth, and tin electrodes. The non-noble nanoparticles exhibit signs of surface oxidation likely formed post-deposition when exposed to air. Nanoparticles generated without hydrogen are found to be primarily polycrystalline and oxidized. To demonstrate the advantages of supplying the reducing agent at generation, we compare to nanoparticles that are generated in nitrogen and sintered in a hydrogen mixture. For bismuth and tin, the crystal quality of the particles after sintering is considerably higher when hydrogen is introduced at particle generation compared to at sintering, whereas for cobalt it is equally effective to only add hydrogen at sintering. We propose that hydrogen present at particle generation prevents the formation of oxide primary particles, thus improving the ability to sinter the nanoparticles to compact and single crystals of metal. This method is general and can be applied to other aerosol generation systems, to improve the generation of size-controlled nanoparticles of non-noble metals with a suitable reducing agent. Copyright © 2018 American Association for Aerosol Research